Analysis of the Internal Control Systems for Delivery of Covid-19 Vaccine in Expedition Service Companies Using Internal and External SWOT Approach (Case Study DHL ID: 2020) - Pratiwi, Sekar Widyastuti; Juhri, Apsada; Nursery Alfaridi S; Irenita, Novembriani; Budiman, Tenaka (Dinasti Publisher, 2024)
In the context of the COVID-19 pandemic, expedited services companies play a pivotal role in the distribution of vaccines, necessitating effective internal control systems. This research utilizes COSO Internal Control Framework and SWOT analysis to examine the internal control system for COVID-19 vaccine delivery within companies. Through qualitative interviews and quantitative analysis of company documents, strengths and weaknesses of the internal control system, as well as external opportunities and threats impacting vaccine distribution, are identified. The study aims to provide recommendations to enhance the internal control system for improved efficiency and effectiveness of COVID-19 vaccine distribution. By contributing insights into vaccine logistics and internal controls, this research supports global efforts to combat the pandemic by ensuring secure and timely delivery of vital vaccines.